2004
DOI: 10.1191/0269215504cr781oa
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of muscle strength and motor fatigue with a knee dynamometer in subjects with multiple sclerosis: a new fatigue index

Abstract: Maximal isometric torque and motor fatigue of knee flexor and extensor muscles can be reliably measured using a knee dynamometer in MS patients. The new FI proved to be a reliable model for MS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 16 publications
2
64
1
2
Order By: Relevance
“…Most studies show that physical or muscular fatigue is higher in MS patients who subjectively reported fatigue than in healthy individuals [17,19,24]. The paradigm was transferred to the cognitive sphere, where cognitive fatigue was conceptualised as decreased performance over an extended time or after challenging effort [2,4,10,20].…”
Section: ■ Behaviour Aspectmentioning
confidence: 99%
“…Most studies show that physical or muscular fatigue is higher in MS patients who subjectively reported fatigue than in healthy individuals [17,19,24]. The paradigm was transferred to the cognitive sphere, where cognitive fatigue was conceptualised as decreased performance over an extended time or after challenging effort [2,4,10,20].…”
Section: ■ Behaviour Aspectmentioning
confidence: 99%
“…Interest in the clinical measurement of fatigue in conditions such as multiple sclerosis (5,(8)(9)(10) amyotrophic lateral sclerosis (6), post polio (11)(12)(13)(14)(15), hereditary motor and sensory neuropathy (16) and Parkinson's disease (17) has increased in the recent past. There are now several published methods of measuring motor fatigue that can be used clinically (5,6,(11)(12)(13)16,17).…”
Section: Introductionmentioning
confidence: 99%
“…As numbers were quite small, it is quite possible that an existing relationship was not identified, although it could also indicate that motor and subjective fatigue are completely different and unrelated constructs. Studies in Multiple Sclerosis have found little evidence of a correlation between motor fatigue and reports of subjective fatigue, mobility and function (Schwid et al, 1999;Surakka et al, 2004). We found no evidence that motor fatigue independently influenced mobility, while muscle strength was confirmed as an important factor associated with mobility (Gylfadottir, Dallimore, and Dean, 2006).…”
Section: Discussionmentioning
confidence: 53%